Too fast to bother? Integrity, instrumentality, and externality factors for early sustainable design implementation in the fast-moving-consumer-goods sector. (15th December 2020) - Park, Curie; Charnley, Fiona; Longhurst, Phil; Bolton, Simon; Evans, Steve
This paper investigates what enables sustainable design implementation from the front-end of new product development (NPD) processes within the fast-moving-consumer-goods (FMCG) industry. Five FMCG cases at varying sustainability maturity levels (SMLs) were selected for survey-based interviews. The identified 11 factors and 32 sub-factors are presented under the three groups of integrity, instrumentality and externality. Balanced focus on Growth and Consumer Insight and Maturity of infrastructure and consumer & market are FMCG specific. The synthesis is presented in a framework explaining the precedence of the Integrity group factors before others. Quantitative analysis reveals that more positive, frequent evidence of factors and sub-factors is observed in higher sustainability maturity cases. The study confirms some of the existing but controversial factors across design and management fields, and uncovers two new FMCG specific factors. The study assists academics and industry practitioners in understanding what to consider when adopting sustainable design in the fast-paced business environment.